Are the correlates of sport participation similar to those of screen time? - Allen, Mark (My University, 2015)
Objective To explore longitudinal and cross-sectional correlates of sport participation and screen time in a nationally representative sample of Australian children. Methods The sample included 3956 child participants taken from the Longitudinal Study of Australian Children. Data were collected in 2004 (age range = 4–5 years) and 2012 (age range = 12–13 years) and included parental estimates of sport participation and total screen time (electronic gaming and television viewing) in addition to demographic, socioeconomic and environmental factors. Results Sport participation and total screen time were inversely correlated (r = − .10). Child demographics (sex, pubertal status, general health, and body mass index [BMI]), socioeconomic (neighborhood socioeconomic position, household income, parental education, and parental BMI) and environmental (neighborhood belonging, neighborhood safety, and neighborhood facilities) factors were related to both outcomes — in most cases a positive [negative] correlation with sport participation yielded a corresponding negative [positive] correlation with total screen time. Conclusion Our findings show that demographic, socioeconomic and environmental factors measured at age 4 predict sport participation and screen time at age 12, and that the correlates of childhood sport participation and childhood sedentary behavior may be more similar than previously estimated.
Keywords: Child Development -- Physical; Child Development -- Behaviour; Childhood and child development; Child Development; Behaviour; Physical; Childhood and child development